Bivariate evaluation of thromboembolism and bleeding in clinical trials of anticoagulants in patients with atrial fibrillation - Kittelson, John M.; Steg, Philippe Gabriel; Halperin, Jonathan L.; Goldenberg, Neil A.; Schulman, Sam; Spyropoulos, Alex C.; Kessler, Craig M.; Turpie, Alexander G. G.; Cutler, Neal R.; Hiatt, William R.; for the Antithrombotic Trials Leadership and Steering (ATLAS) Group (Thrombosis and Haemostasis, 2016)
Clinical trials of antithrombotic therapy require a cohesive assessment of benefit and risk. A new graphical method to represent the bivariate relation of benefit and risk in trials of antithrombotic drugs is described and illustrated using published data from the four major registration clinical trials of non-vitamin K oral anticoagulants (NOACs) totalling 71,683 patients for prevention of thromboembolic events (TE) in patients with atrial fibrillation (RE-LY, ROCKET AF, ARISTOTLE, and ENGAGE-AF TIMI48). A curve representing a null hypothesis defines a region of benefit on a two-dimensional plane. Trial results are summarised by a rectangle defined by standard 95 % confidence intervals (CI) for thrombosis and bleeding risks. Benefit is judged by whether the confidence rectangle contains the null curve. The treatment effect is measured by the distance from the null curve to the opposing corners of the confidence rectangle (termed “corner distance (CD)”). Across trials NOACs reduced the absolute risk of TE compared to warfarin by 0.30 % (95 % CI: –0.56 % to –0.05 %) and reduced major bleeding by 0.88 % (95 % CI: –1.26 % to –0.51 %). Bivariate evaluation showed NOAC superiority to warfarin overall and elucidated dose differences; low dose edoxaban increased bivariate TE-bleeding risk 0.08 % (CD = –0.85 % to 0.78 %), whereas high dose edoxaban reduced risk 1.41 % (CD = –2.07 % to –0.70 %). In conclusion, bivariate evaluation facilitates visual assessment of the safety-efficacy profile of antithrombotic drugs. Its application to trials in atrial fibrillation found NOACs superior to warfarin without substantial differences between agents.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Clinical trial; net clinical benefit; noninferiority; meta-analysis